Prevalence of Alcohol Consumption among Adults & Elderly- a Community based Study in Uttarakhand - Ravi, Satish; Kishore, Surekha; Pasi, Rachna; Verma, Neha (Indian Journal of Community Health, 2019)
Background: Alcohol is one of the leading causes of the death and disability globally. About two billion people worldwide consume alcoholic beverages and about one-third (nearly 7.6 million) are likely to have one or more diagnosable alcohol use disorders. In India, the economic returns from alcohol override public health issues with the situation being one of “getting less and losing more”. Aims & Objectives: To find out the prevalence of alcohol consumption in relation to socio-demographic characteristics among adults and elderly population of Uttarakhand. Methods and materials: This is a cross sectional study. In this study we included four different geographic settings (urban, rural, town and slum) of Uttarakhand. A simple random methodology was adopted. Results: Out of 400 participants interviewed, alcohol consumption was reported higher in 30-49 years age group (45%), married (38%), employed (58%), males (72%), residing in rural areas (43%). Conclusion: In Uttarakhand percentage of alcohol consumption is higher among middle age group (30-49 year). Males are more alcoholic than females.